Bioethanol production from sesame (Sesamum indicum L.) plant residue by combined physical, microbial and chemical pretreatments. (February 2020) - Kumar, Pankaj; Kumar, Vinod; Kumar, Sachin; Singh, Jogendra; Kumar, Piyush
Graphical abstract: Highlights: The first report on bioethanol production from sesame plant residues. Three combined pretreatments including physical, microbial, and chemical were done. Kinetic modeling of pretreatment and bioethanol production process was done. The maximum bioethanol yield was 1.90 g·L −1 in the finest (400 µm) particle size. Abstract: This study explored the potential of sesame ( Sesamum indicum L.) plant residue (SPR) for bioethanol production. Three particle sizes, including 400, 850 and 1300 µm of SPR, were subjected to microbial degradation by Phanerochaete chrysosporium followed by 1% H2 SO4 pretreatments. FTIR and HPLC analyses showed that the combined pretreatment which begins with microbial followed up by acid degraded SPR in the finest particle size (400 µm) resulted in the maximum contents of reducing sugars (370.23 mg·g −1 ). Kinetics studies of the pretreatment process also confirmed the maximized rate of hemicellulose and lignin reduction with reducing sugars production. The logistic model had better fitness as compared to the modified Gompertz model to predict bioethanol production. SPR gave a maximum of 1.90 g·L −1 bioethanol yield after 60 h of fermentation using Saccharomyces cerevisiae . This study is the first report on bioethanol production from SPR, which proposed its suitability for sustainable energy production.